Development of an innovative bio-binder using Asphalt-rubber technology - Peralta, J. (2013)
This research work evaluates several parameters that can affect Asphalt Rubber (AR) binder performance and applies the AR technology to the development of an innovative renewable bio-binder that can fully and cost-effectively replace asphaltic bitumen derived from petroleum in flexible pavement construction. The “Binder Accelerated Separator” method was used to divide the constituents of the Asphalt Rubber and bio-binder (residual binder and swelled rubber). The physical and chemical changes in the Asphalt Rubber and bio-binder and in the residual binders (residual bitumen and residual bio-oil) were evaluated. The results demonstrate that the produced bio-binder is suitable for use in flexible pavements with properties comparable to those of conventional and Asphalt Rubber binders.